Images of Ancient Egypt in unpublished memoirs of Russian women (female) travelers at the turn of the XIX–XX centuries - V. V. Vasilik; D. A. Kharina (Вестник Самарского университета: История, педагогика, филология)
The article examines the peculiarities of the historical perception of Ancient Egypt by Russian women travelers. The author analyzes unpublished sources from the funds of the Russian State Historical Archive, Russian State Archive of Literature and Arts, and the Institute of Russian Literature (Pushkinskij dom) of the Russian Academy of Sciences – letters and travel notes of Russian travelers compiled in the late XIX – early XX century. Within the studies of the Russian oriental discourse during this period, the historiosophical question of the place of the Russian Empire and its culture in the Western-Eastern dichotomy has recently been re-raised. The authors compare the perception of Russian travelers with English and French ones. Sharing their impressions of visiting Luxor, Giza and Aswan and getting acquainted with the history of Ancient Egypt, the authors of travel notes come to an unexpected conclusion at first glance that Russian culture, history and traditions date back to Ancient Egypt. In their interpretation, Ancient Egypt appears to be the cradle of Russian civilization. The authors studie the motivation of Russian travelers in their desire to see themselves as descendants of the great pharaohs and why they believe that Russian civilization has its roots in Ancient Egypt. The authors uses modern historical methodology: semiotics, imagology, E. Said’s concepts of «Orientalism», the theory of Yu. Lotman. In conclusion, the author of the work summarizes the results and points out that travel and exploration of Ancient Egypt played an important role in shaping the ideas about the origin and cultural heritage of the Russian people